A Large Central Bank Balance Sheet? The Role of Interbank Market Frictions - Dominik Thaler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Recent quantitative easing (QE) policies implemented over the course of the Great Recession by the major central banks have had a profound impact on the working of money markets, giving rise to large excess reserves and pushing down key interbank rates against their floor .the interest rate on reserves. With macroeconomic fundamentals improving, central banks now face the dilemma as to whether to maintain this large balance sheet/floor system, or else to reduce balance sheet size towards pre-crisis trends and operate traditional corridor systems. We address this issue using a relatively simple New Keynesian model with two distinct features: heterogeneous banks that trade funds in an interbank market, and matching frictions in the latter market. We show that a large balance sheet allows for ampler .policy space.by widening the average distance between the interest on reserves and its effective lower bound. Nonetheless, a lean-balance-sheet regime that resorts to temporary QE in response to recessions severe enough for the lower bound to bind achieves similar stabilization and welfare outcomes as a large-balance-sheet regime in which interest-rate policy is the primary adjustment margin thanks to the larger policy space. At the same time, the effectiveness of QE through the channel we model is limited. In line with the empirical evidence, the marginal effect vanishes as the balance sheet becomes very big.
Keywords: E20; E30; G10; G20; 330; central bank balance sheet; interbank market; search and matching frictions; reserves; zero lower bound